Generic language and judgements about category membership: Can generics highlight properties as central? - Hollander, Michelle A. (Lang Cogn Process, 2009)
Many languages distinguish generic utterances (e.g., “Tigers are ferocious”) from non-generic utterances (e.g., “Those tigers are ferocious”). Two studies examined how generic language specially links properties and categories. We used a novel-word extension task to ask if 4- to 5-year-old children and adults distinguish between generic and specific language, and judge that predicating a property of a depicted novel animal using generic language (e.g., “Bants have stripes”), rather than non-generic language (e.g., “This bant has stripes”) implies a more kind-relevant connection between category and property. Participants were asked to endorse an extension of the label taught to a novel animal matching the target instance on either overall similarity or the mentioned property. Wording was found to have a significant effect on responses for both age groups. Altogether, the results of these studies suggest that the generic may be a default interpretation for young children, who need to learn the semantics of specific and set-theoretic expressions.